2021
DOI: 10.1159/000520494
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Accuracy of ABCD-10 and SCORTEN in Predicting the In-Hospital Mortality of Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis: A Multi-Institutional Study from Central China

Abstract: <b><i>Background:</i></b> The newly described ABCD-10 (age, bicarbonate, cancer, dialysis, 10% body surface area [BSA]) is a 5-item mortality prediction model for patients with Stevens-Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN). It was developed in the United States, has at present been externally tested only in the United States, Spain, and Singapore, and remains to be validated in resource-restricted settings. We sought to compare the accuracy of ABCD-10 and Score of Toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Other alternatives to SCORTEN have been proposed; the most popular being ABCD-10 which stands for age, bicarbonate, cancer, dialysis, 10% BSA. Studies comparing the accuracy of SCORTEN and ABCD-10 have largely found SCORTEN to be superior or equivalent to ABCD-10 ( 18 20 ). ABCD-10, like SCORTEN, also requires calculation of TBSAI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other alternatives to SCORTEN have been proposed; the most popular being ABCD-10 which stands for age, bicarbonate, cancer, dialysis, 10% BSA. Studies comparing the accuracy of SCORTEN and ABCD-10 have largely found SCORTEN to be superior or equivalent to ABCD-10 ( 18 20 ). ABCD-10, like SCORTEN, also requires calculation of TBSAI.…”
Section: Discussionmentioning
confidence: 99%
“…A 2006 study found that delay-adjusted SCORTEN scores were comparable to crude scores but that there was significant difference in score between days 1 and 4 ( 19 ). Another study showed that SCORTEN and ABCD-10 performed differently depending on when after admission data were collected ( 20 ). Our model also does not take time point into account; however, we believe that the use of only lab values as continuous variables may allow for stability over time.…”
Section: Discussionmentioning
confidence: 99%
“…While ABCD-10 has good discriminatory ability, multiple studies have showed that it underperforms in comparison to SCORTEN ( 3 , 7 , 15 , 16 ). Specifically, one retrospective cohort study in Singapore found that in both patients treated with supportive care or immunomodulatory therapy, ABCD-10 underestimated mortality at lower score ranges and overestimated mortality at higher score ranges ( 15 ).…”
Section: Strengths and Weaknesses Of Abcd-10mentioning
confidence: 99%
“…The SJS/TEN-specific severity-of-illness score (SCORTEN) has been the mainstay of measurements to define mortality risk of SJS/TEN in both clinical practice and research ( 44 ). The ABCD-10 (age, bicarbonate, cancer, dialysis, 10% BSA) is another cross-sectional severity scoring system that incorporated end-stage renal disease and was shown to perform slightly inferior to SCORTEN by underestimating mortality ( 45 , 46 ). Another study proposed adding inflammatory markers to the SCORTEN to improve predictive accuracy.…”
Section: Updates In Diagnosis Assessment and Causalitymentioning
confidence: 99%